Evaluation of macular neovascularization activity in pathological myopia: a comparison between optical coherence tomography and OCT-angiography - Li, Xin; Jing, Ruixia; Li, Xue; Wang, Zhen (Frontiers in Medicine, 2023)
Purpose The purpose of this study was to suggest a novel approach to assessing the activity of macular neovascularization (MNV) in pathological myopia (PM) by comparing optical coherence tomography (OCT) with OCT-angiography (OCT-A). Methods The Zeiss Cirrus HD-5000 was used to obtain OCT and OCT-A images of PM-MNV. The objective was to examine the characteristics of PM-MNV lesions and investigate the relationship between PM-MNV activity and changes in retinal structure in 54 patients (54 eyes). To analyze the OCT parameters associated with PM-MNV activity and their clinical significance in terms of sensitivity and specificity, we used OCT-A as a reference. Results This study included 72 patients (72 eyes), of whom 54 had good image quality and were considered for analysis. The study evaluated various OCT characteristics of MNV lesions, including the elevation of an external limiting membrane (ELM), ellipsoidal zone (EZ), retinal pigment epithelium (RPE) elevation, and EZ/RPE interruption, to identify possible parameters associated with PM-MNV activity. The interobserver consistency was found to be almost perfect. In the evaluation of PM-MNV activity, the sensitivity of ELM elevation, EZ interruption, and RPE interruption was found to be 66.7% (low), 88.4% (high), and 95.6% (high), respectively. However, the specificity was found to be 71.4% (moderate), 71.4% (moderate), and 25.4% (poor), respectively. This indicates that the current evaluation methods are not accurately assessing PM-MNV activity. We developed a new comprehensive method that used EZ interruption as the primary parameter and ELM elevation and RPE interruption as secondary parameters to evaluate PM-MNV activity with a sensitivity of 97.8% and a specificity of 85.4%. Conclusion In PM-MNV, a novel comprehensive diagnostic method combining EZ interruption, ELM elevation, and RPE interruption might be a valuable indicator to evaluate PM-MNV activity.